2022
DOI: 10.1093/burnst/tkac008
|View full text |Cite
|
Sign up to set email alerts
|

The Notch pathway attenuates burn-induced acute lung injury in rats by repressing reactive oxygen species

Abstract: Background Acute lung injury (ALI) is a common complication following severe burns. The underlying mechanisms of ALI are incompletely understood; thus, available treatments are not sufficient to repair the lung tissue after ALI. Methods To investigate the relationship between the Notch pathway and burn-induced lung injury, we established a rat burn injury model by scalding and verified lung injury via lung injury evaluations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Enrichment analysis through GO-BP shows significant involvement of these genes in oxidative stress, pyridine-containing compound metabolic process, and reactive oxygen species metabolic process. Although, to our knowledge, there is no exact experimental evidence of ferroptosis in burns, ROS accumulation and lipid peroxidation can be observed in the serum of burn patients (24,25). Antioxidants were shown to significantly reduce injury and edema after burns (26-28).…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment analysis through GO-BP shows significant involvement of these genes in oxidative stress, pyridine-containing compound metabolic process, and reactive oxygen species metabolic process. Although, to our knowledge, there is no exact experimental evidence of ferroptosis in burns, ROS accumulation and lipid peroxidation can be observed in the serum of burn patients (24,25). Antioxidants were shown to significantly reduce injury and edema after burns (26-28).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they delve into the diverse molecular mechanisms and signaling pathways that modulate oxidative stress, and through this avenue, several novel regulatory molecules and pathways have been identified that can ameliorate ECs damage by inhibiting oxidative stress, thereby providing new avenues for improving the clinical status of ALI/ARDS. For instance, Cai et al ( Cai et al, 2022 ) revealed in a study on burn-induced acute lung injury (ALI) that activation of the Notch pathway in pulmonary microvascular endothelial cells (PMVECs) significantly reduced ROS production and cell apoptosis by downregulating NOX4 expression. This study elucidated the critical role of the Notch-NOX4 signaling pathway in regulating ROS generation and cell apoptosis in PMVECs, thus offering a new therapeutic target for burn-induced ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Notch1 signaling pathway has been shown to reduce oxidative stress in injured tissues ( Cai et al, 2022 ). The thioredoxin (TRX) system is a key antioxidant system against oxidative stress ( Lu and Holmgren, 2014 ).…”
Section: The Mechanisms Of Tp-induced Hepatotoxicitymentioning
confidence: 99%